2015
DOI: 10.1109/tasc.2014.2379116
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Critical Properties of Alloyed Nb-Sn Wires After Proton Irradiation at 65 MeV and 24 GeV

Abstract: A recent proton irradiation study on Ta and Ti alloyed industrial multifilamentary Nb 3 Sn wires has now been extended to fluences up to 1.38 × 10 21 p/m 2 , the Bragg peak region being located outside of the wire. In the present work, magnetization measurements were performed up to 14 K and 10 T, to follow and determine with more precision the development of the upper critical field B c2 with fluence. It was found that the critical temperature, T c , decreases linearly with increasing fluences, about 3% up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…However, even in that case η would remain significantly lower than in the other materials, which Table 3 summarizes critical current densities achieved by various irradiation techniques. The results after proton or neutron irradiation are quite similar although J c is slightly higher for protons and obtained at a smaller fluence, both of these effects are also observed in Nb 3 Sn [14,66,67]. The only exception is the 11 compound, where low energy (190 keV) protons [59] lead to significantly higher currents than neutrons.…”
Section: Critical Currentssupporting
confidence: 52%
See 1 more Smart Citation
“…However, even in that case η would remain significantly lower than in the other materials, which Table 3 summarizes critical current densities achieved by various irradiation techniques. The results after proton or neutron irradiation are quite similar although J c is slightly higher for protons and obtained at a smaller fluence, both of these effects are also observed in Nb 3 Sn [14,66,67]. The only exception is the 11 compound, where low energy (190 keV) protons [59] lead to significantly higher currents than neutrons.…”
Section: Critical Currentssupporting
confidence: 52%
“…A significantly smaller decrease rate was found in Nb 3 Sn (0.35 × 10 −22 Km 2 ) [13], which is a fully gaped superconductor and a decrease in the electronic DOS at the Fermi level is responsible in that case. However, although a comparison of the changes induced by a particular radiation is useful for testing the suitability of a certain material in the respective environment (fusion [10,62] or accelerator magnets [14,65,66]), it is a bit problematic for a comparison of the material's sensitivity to disorder for drawing conclusions on the underlying mechanisms, since the introduced disorder itself depends on the material. The number of displacements per atom (dpa) is a more suitable measure for this purpose, although the morphology of the defects is expected to be important as well with single displaced atoms being the most efficient scattering centers and hence reducing the transition temperature the most at a given dpa.…”
Section: Transition Temperaturementioning
confidence: 99%
“…To our knowledge such a performance of industrially produced multifilamentary Nb 3 Sn is unprecedented in literature, and the data obtained from our extensive magnetometry study on sequentially irradiated short wire samples strongly indicate that even higher critical current densities are attainable. In fact, recent results obtained from a proton irradiation study on the same Ti-alloyed RRP wire show a J c enhancement of 100% relative to the unirradiated state at an applied field of 10 T. 23 The essential change induced by fast neutron radiation is the addition of point-pinning centers, leading to an increase of the maximum volume pinning force and to a shift of the pinning force peak towards higher reduced field values. This point-pinning contribution results in a significant enhancement of J c over a wide field range, as shown in Figure 4.…”
Section: Discussionmentioning
confidence: 96%
“…In order to predict the effects of the complex radiation damage in the quadrupole magnets of the HL-LHC accelerator, we have recently performed a series of investigations on the same Nb 3 Sn wires, which were irradiated by fast neutrons (>0.1 MeV) [3,4] and by protons (65 MeV and 24 GeV) [5][6][7]. These works were performed on RRP and powder-in-tube (PIT) type multifilamentary Nb 3 Sn wires from the same batch and confirmed that high energy irradiation at low fluences ( 3×10 22 n m −2 and 2×10 21 p m −2 ) leads to a slight, linear decrease of T c and to a marked increase of J c .…”
Section: Introductionmentioning
confidence: 99%